Dynamic Pricing and Traffic Engineering for Timely Inter-Datacenter Transfers - Jalaparti, Virajith; Bliznets, Ivan; Lucier, Brendan; Kandula, Srikanth; Menache, Ishai (Sigcomm 2016, 2016)
As more business moves to the cloud, inter-datacenter bandwidth becomes an ever more valuable and congested resource. This bandwidth is typically sold using a fixed price per GB, and transfers are scheduled using traffic engineering mechanisms. However, this separation between the economic and engineering aspects of the problem makes it difficult to steer customer demand to lightly loaded paths and times, which is important for managing costs (typically proportional to peak usage) and providing service guarantees. To address these issues, we design and evaluate Pretium – a framework that combines dynamic pricing with traffic engineering for inter-datacenter bandwidth. In Pretium, users specify their required rates or transfer sizes with deadlines, and a price module generates a price quote for different guarantees (promises) on these requests. The price quote is generated using internal prices (which can vary over time and links) which are maintained and periodically updated by Pretium based on history. A supplementary schedule adjustment module gears the agreed-upon network transfers towards an efficient operating point by optimizing time varying operation costs. Using traces from a large production WAN, we show that Pretium achieves up to 80% of the social welfare of an offline oracular scheme, significantly outperforming usage-based pricing alternatives.